Mapping and visualization of global research progress on autophagy in metabolic dysfunction-associated steatotic liver disease and metabolic syndrome: a bibliometric analysis (2009–2024) - Liu, Xing; Li, Xiang (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to delineate the current trends and hotspots in autophagy research related to metabolic syndrome (MetS) and metabolic dysfunction-associated steatotic liver disease (MASLD), with the aim of guiding future investigations in this area.MethodsThis study extracted research on autophagy in MetS and MASLD from the Web of Science Core Collection (WoSCC) database. Review articles were systematically excluded to focus on original research contributions. A bibliometric analysis and visualization were conducted using VOSviewer 1.6.20, CiteSpace 6.3.R1, and R 4.3.3.ResultsThe study included 1,114 articles from 1,220 institutions across 42 countries/regions, demonstrating a significant increase in research output from 2009 to 2024. China led with 506 publications, followed by the USA and Korea. The Egyptian Knowledge Bank constitutes a consortium of institutions operating within the national research framework, with one institution designated as the primary publishing entity. Notably, the journal Nature has emerged as the most frequently cited publication. Singh Rajat received the highest number of citations (3,610), while Marycz Krzysztof was the most prolific author. The most cited article, published in 2009, was titled “Autophagy regulates lipid metabolism.” Keyword trends have shifted from earlier topics such as “phosphorylation” and “gene-expression” to more recent terms like “lipid accumulation” and “mitophagy.” Burst keyword analysis indicated that “liver fibrosis,” “modulation,” “gut microbiota,” and “lipotoxicity” have emerged as significant topics.ConclusionsThis study has elucidated the protective role of autophagy in MASLD and MetS. Future research is anticipated to concentrate on the activation of autophagy in the context of natural product drug discovery, the exploration of underlying molecular mechanisms, the regulation of fatty acid metabolism, and the development of functional nutritional supplements, among other relevant areas.